Analysis of The Impact of Macroeconomic Variables on The Sharia Index of Indonesia - Rahmat Fitriansyah; Darwanto Darwanto (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
This study intends to analyze the impact of macroeconomic variables on the indonesian sharia stock index. using vector error correction modeling (vecm) and variable money supply, industrial production index, consumer price index, exchange rate, bank interest rates, and indonesian sharia bank certificates as independent variables. findings / originality: the results show that the industrial production index, the exchange rate has a significant positive effect and the variable money supply, the consumer price index, and the sharia bank indonesia certificate have a significant negative effect on issi. granger's causality results prove that only the money supply and industrial production index have causality, but there is a one-way relationship including the indonesian syariah bank certificate to the money supply, the exchange rate, and the consumer price index. bank interest rates on sharia indonesia bank certificates, sharia indonesia bank certificates against consumer price indexes and exchange rates, and industrial production index.